2013
DOI: 10.1155/2013/947980
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Green Propolis Compared to Miconazole Gel in the Treatment ofCandida-Associated Denture Stomatitis

Abstract: Aim. To evaluate the efficacy of Brazilian green propolis in comparison to miconazole gel in the treatment of Candida-associated denture stomatitis. Methods. Forty-five denture stomatitis patients, with palatal mucosa erythema levels classified according to Newtons's criteria and with positive culture to Candida spp., were randomly divided into three treatment groups: 15 received miconazole gel 2%, 15 received propolis gel 2,5%, and 15 received propolis 24% for mouthwash. After four daily use lasting two weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 24 publications
3
57
0
7
Order By: Relevance
“…It contains resinous substances collected by honey bees, from various plants, thus forming a complex of biologically active substances [16]. Several research groups revealed high antifungal potential of propolis against Candida clinical isolates [26][27][28][29]. The results of our investigation confirmed high fungicidal activity of propolis against all strains tested, but only in the case of one of four analyzed samples.…”
Section: Discussionsupporting
confidence: 71%
“…It contains resinous substances collected by honey bees, from various plants, thus forming a complex of biologically active substances [16]. Several research groups revealed high antifungal potential of propolis against Candida clinical isolates [26][27][28][29]. The results of our investigation confirmed high fungicidal activity of propolis against all strains tested, but only in the case of one of four analyzed samples.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, it may be questioned whether the treatment duration or use of higher concentrations could interfere with the antifungal action. Capistrano et al [19] obtained clinical improvement in prosthetic stomatitis lesions, but without total remission of the lesions in all patients, in a study with a methodology similar to the present study.…”
Section: Discussionsupporting
confidence: 68%
“…In vitro models showed that the 1% alcoholic propolis extract was sufficient to completely inhibit the growth of one million Candida cells per millilitre of sample [22]. The efficacy of propolis gel was demonstrated and compared to the use of miconazole oral gel in clinical studies [19, 23]. …”
Section: Introductionmentioning
confidence: 99%
“…Four studies pooled to evaluate the effect of imidazole on clinical stomatitis found no effect on the remission of clinical stomatitis (RR = 0.98, 95% CI = 0.85–1.13). There was no heterogeneity ( P = .26; I 2 = 26%), and no effect was found for mycological assessment (RR = 0.77, 95% CI = 0.56–1.07; P = .96, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%